Anatomy and Morphological Study of Mentigi Gunung (Vaccinium varingiaefolium (Blume) Miq.) in Area of Mount Batok-Indonesia - Sholikhah, Annisa; Aryani Dian, Farida; Listyorini, Dwi (KnE Life Sciences, 2017)
Mentigi Gunung (Vaccinium varingiaefolium (Blume) Miq.), endemic plant of Java which dominates sub-alpine area of Mount Batok. This study aimed to characterize plant’s anatomical and morphological structure for conservation purpose. Microscopic and macroscopic approaches used for organs observation. Morphological observation showed that this plant has a tap root, circular stem with lenticels on its surface. It has red young stem with a lot of trichomes, brown old stem, oval leaves with integer margins. Leaves have stone cells, cuticles, idioblasts. Young leaves are red and turn green. Flowers are purple with five sepals, five petals, 10 androecium and one syncarp gynoecium. Trichomes spread all over flower structures. The type of microspore is tetraeder. The gynoecium sits on the receptacle composed of five carpellum with inpherus ovulus. The fruits are green, globular, with trichomes and turn black when ripe. It has stone cells with purple cytoplasm and golden brown seeds. Vascular bundle is opened collateral type; the type is parasitic with kidney-shaped guard cells. Keywords: Anatomy; morphology; mentigi gunung; Vaccinium varingiaefolium (Blume) Miq.